Carbon dioxide capture and utilization: using dinuclear catalysts to prepare polycarbonates. (6th October 2015) - Yi, N.; Unruangsri, J.; Shaw, J.; Williams, C. K.
Abstract : The copolymerization of epoxides, including cyclohexene oxide and vinyl-cyclohexene oxide with carbon dioxide are presented. These processes are catalyzed using a homogeneous di-zinc complex that shows good activity and very high selectivities for polycarbonate polyol formation. The polymerizations are investigated in the presence of different amounts of exogenous reagents, including water, diols and diamines, as models for common contaminants in any carbon dioxide capture and utilization scenario.